2014
DOI: 10.1089/jpm.2013.0224
|View full text |Cite
|
Sign up to set email alerts
|

Rehospitalization of Older Adults Discharged to Home Hospice Care

Abstract: Background: Acute hospital readmission of older adults receiving hospice care is not aligned with hospice goals. Objective: To identify factors associated with 30-day readmission among older adults newly discharged to hospice. Design/Subjects: Medical record review of 59 patients, 19 readmitted within 30 days and 40 randomly selected controls not readmitted, from 206 patients newly discharged to home hospice care between February 1, 2005 and January 31, 2010. Measures/Analysis: Information was collected about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 11 publications
(10 reference statements)
0
29
0
Order By: Relevance
“…41,43,44 From this review, we may also derive the need to continue implementing and evaluating cares that are being valued as very positive by patients and family caretakers for a positive transition between the hospital and the home. Among others, they highlight the following: education of the dyad during hospital discharge, 35,38,45 telephone follow up, 46,47 homecare teams, 48,49 and support groups of patients and caregivers. 30,31 Regarding these types of support, Stajduhar et al, 50 comment that the nature of the experiences of the dyads in PC can vary according to the structure of the health systems and of the social services, of access to services, and of the types of support available.…”
Section: Discussionmentioning
confidence: 99%
“…41,43,44 From this review, we may also derive the need to continue implementing and evaluating cares that are being valued as very positive by patients and family caretakers for a positive transition between the hospital and the home. Among others, they highlight the following: education of the dyad during hospital discharge, 35,38,45 telephone follow up, 46,47 homecare teams, 48,49 and support groups of patients and caregivers. 30,31 Regarding these types of support, Stajduhar et al, 50 comment that the nature of the experiences of the dyads in PC can vary according to the structure of the health systems and of the social services, of access to services, and of the types of support available.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between PCP involvement and ED or hospital admission was mixed. Although two studies found that PCP involvement was associated with lower odds of ED or hospital admission, two studies reported the opposite, and another two found no association . A Canadian study of 8,702 individuals with cancer concluded that greater family physician continuity was associated with lower ED admission rates .…”
Section: Resultsmentioning
confidence: 99%
“…PCP involvement was not uniformly measured across all studies (Table ). Some studies examined the number of PCP outpatient, home, or telephone contacts during a specified time frame. Others assessed whether a PCP was involved in participants' care in different settings (e.g., home, hospice, hospital) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Acute hospital readmission for patients in hospice is an active area of research. 2 In addition to caring for already dying patients, hospitalists also diagnose and manage new imminently life-threatening conditions and their devastating complications.…”
mentioning
confidence: 99%